2012
DOI: 10.1037/a0027659
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acculturation and discrimination on mental health symptoms and risk behaviors among adolescent migrants in Israel.

Abstract: This study examines the role of acculturation, perceived discrimination, and self-esteem in predicting the mental health symptoms and risk behaviors among 1.5 and second generation non-Jewish adolescents born to migrant families compared with native-born Jewish Israeli adolescents in Israel. Participants included n = 65 1.5 migrant adolescents, n = 60 second generation migrant adolescents, and n = 146 age, gender, and socioeconomic matched sample of native-born Jewish Israelis. Participants completed measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 90 publications
4
36
1
1
Order By: Relevance
“…[5] The migrant adolescents have reported worse mental health symptoms and highly engaged in risk behaviors compared with the native Israel counterparts, it was even significantly higher when compared with the second generation migrant adolescents. [6]…”
Section: Migration and Mental Health: An Interfacementioning
confidence: 99%
“…[5] The migrant adolescents have reported worse mental health symptoms and highly engaged in risk behaviors compared with the native Israel counterparts, it was even significantly higher when compared with the second generation migrant adolescents. [6]…”
Section: Migration and Mental Health: An Interfacementioning
confidence: 99%
“…Similarly, a study comparing immigrant adolescents with native-born Israeli adolescents found that in general, immigrant youth exhibited lower wellbeing than native-born adolescents. More specifically however, assimilated immigrant youth reported higher mental health issues than adolescent immigrants who were integrated [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an orientation towards both ethnic and majority identity has been shown to be associated with less perceived discrimination [25,26], and a less distressing adaptation process of immigrants [27]. The health effects of assimilation and separation are less clear, with both having been associated with increased [28,29] as well as decreased mental health [30,31].…”
Section: Introductionmentioning
confidence: 99%